AN EXAMINATION OF THE RELATIONSHIP BETWEEN BASKETBALL FREE-THROW PERFORMANCE AND COGNITIVE PERFORMANCE - GÖÇMEN, RECEP (FUTURE ACAD, 2018)
The purpose of present study was to examine the relationship between basketball free-throw performance and cognitive performance. The comparison of the cognitive performance of basketball players with low and high free throw performance was also the second aim of the study. A total of twenty-four male basketball players aged 18-24 years voluntarily participated in the study. Cognitive performance was evaluated with attention, sensory motor coordination and spatial perception tests. For the five-throw test, participants performed 10 shots within 3 sets (total 30 shots). The statistical analysis detected no statistically significant correlation between the Cognitrone Test, Mental Rotation and Sensomotor Coordination variables and free throw performance (p> .05). Similarly, no statistically significant difference was detected between the Cognitrone test, Mental Rotation and Sensomotor Coordination Test variables in comparison of cognitive characteristics of low and high performer in free throw performance. There was a low moderate positive correlation between COG and MR components (r = .47, r = .44, p <.05), a moderate positive correlation between COG and MR components (r = .58, p <.05) and a low negative correlation between MR and SMK components (r = -. 40 and r = 45, p <.05). Hence, the present study has determined that there is no statistically significant relationship between cognitive performance and basketball free- throw performance, and in the cognitive performance between low and high free-throw performers. (C) 2018 Published by Future Academy www.FutureAcademy.org.UK
Keywords: Basketball; free throw; attention; spatial perception; sensomotor coordination